Dynamics of Information Systems Theory and Applications - Hirsch, Michael; Pardalos, Panos M.; Murphey, Robert (Springer Optimization and Its Applications,, 2010)
"Dynamics of Information Systems" presents state-of-the-art research explaining the importance of information in the evolution of a distributed or networked system. This book presents techniques for measuring the value or significance of information within the context of a system. Each chapter reveals a unique topic or perspective from experts in this exciting area of research. These newly developed techniques have numerous applications including: the detection of terrorist networks, the design of highly functioning businesses and computer systems, modeling the distributed sensory and control physiology of animals, quantum entanglement and genome modeling, multi-robotic systems design, as well as industrial and manufacturing safety. This volume is intended for graduate students and researchers interested in the most recent developments in information theory and dynamical systems, as well as scientists in other fields interested in the application of these principles to their own area of study.